Transition to Agile method without Agile-compliant performance appraisal? - Md Rejab, Mawarny; Omar, Mazni; Ahmad, Mazida; Hassan, Syahida (IP Publishing LLC, 2018)
Changes in software development methods should lead to revision and reformation of an organization’s performance appraisal system. Several organizations, however, have done a transition to Agile software development methods without reforming the organization’s performance appraisal. The performance appraisal should be aligned with Agile values, principles, and practices, which advocate interactions, collaborations, teamwork, and knowledge transfer. This research aims to reform an Agile-compliant performance appraisal with the following objectives: i) to determine assessment criteria of an Agile- compliant performance appraisal, ii) to construct an Agile-compliant performance appraisal model, iii) to validate an Agile- compliant performance appraisal model that aligns with Agile values and practices. This research comprises of four main phases which are theoretical study, expert reviews, surveys, and evaluation of the model. Expert reviews on components of Agile- compliant performance appraisal and surveys among Agile practitioners will lead to the development of an Agile-compliant performance appraisal model. An Agile compliant performance appraisal model provides new insights on how to evaluate Agile team members in fairly and consistent manner. This indirectly increases the motivation amongst team members and tends to produce a capable workforce to perform at a higher level.